Morphological analysis of astrocytoma - Qaisrani, Abdul Rehman; Shaheen, Uzma; Nazir, Sadia; Jahan, Naseem; Saleem, Muhammad Wahid; Ashraf, Zohaib (Pakistan Journal of Physiology, 2020)
Background: Astrocytoma is the most common brain tumour in adults. It is the second common tumour of CNS in children. The purpose of this study was to provide preliminary data on morphological patterns of astrocytoma in Pakistan. Methods: This was a descriptive cross-sectional study on diagnosed cases of astrocytoma admitted in Neurosurgery Ward, Lahore General Hospital, Pakistan. Biopsies were examined histologically using paraffin sections. Histopathological grading of astrocytoma was done according to WHO classification. Results: Out of total 40 cases, Glioblastoma multiforme (GBM) was the most common tumour accounting for 16 (40%) cases. Diffuse astrocytoma was the second common tumour seen in 13 (32.5%) cases, 9 (22.5%) were anaplastic astrocytoma, and 2 (5%) cases were diagnosed as pilocytic astrocytoma. Males were slightly more affected than females with a ratio of 1.6:1. Maximum number of cases (25%) were found in the 3rd decade and then in 5th, 6th and 7th decade (17.5%) each. Least number (2.5%) of cases were found in 1st decade of life. Conclusion: Glioblastoma multiforme is the most common astrocytic brain tumour in adults, and pilocytic astrocytoma is the least common brain tumour. Pak J Physiol 2020;16(3):22–4